TUBGCP2 variants cause lissencephaly spectrum disorders: a case report and literature review - Yu, Tao; Yu, Miao; Liu, Xueyan; Wang, Hua (Frontiers in Pediatrics, 2025)
BackgroundTUBGCP2 variants are associated with the LIS spectrum disorders, but its pathogenesis remains unclear. To retrospectively analyze the clinical features and genetic information of patients having lissencephaly spectrum disorders associated with TUBGCP2 variants.MethodsClinical and genetic data of a patient diagnosed with TUBGCP2-related lissencephaly spectrum disorder at the Department of Pediatric Neurology, Shengjing Hospital, in March 2022 were collected. Furthermore, we reviewed previously reported literature on patients with the same gene variation.ResultsA 6-year-old female patient presented with microcephaly (head circumference: 46 cm, Z score: <−3), narrow forehead, thick eyebrows, bulbous nose, smooth philtrum, widened and separated teeth, speech and motor developmental delay, intellectual disability, and seizures. Brain magnetic resonance imaging showed pachygyria in the temporal, parietal, and occipital lobes. Gene testing identified hemizygous variation in TUBGCP2 (missense variants: c.178 C>T, c.538T>C, and maternal exon variant: 2–14 deletion). A literature search revealed seven patients with lissencephaly spectrum disorders associated with TUBGCP2 variants, including eight gene variation types. Moreover, the TUBGCP2 variants were found to cause lissencephaly spectrum diseases, with the main clinical manifestations being microcephaly, lissencephaly (including agyria, pachygyria, or subcortical band heterotopia), dysmorphic facial features (e.g., narrow forehead, thick eyebrows, bulbous nose, prominent ears, and widened and separated teeth), and developmental delay, with or without seizures.ConclusionOur study expands the genotype of this brain malformation disorder associated with TUBGCP2 variants by presenting the first case of TUBGCP2 variants causing lissencephaly spectrum disorders in China.